Description of two new species of Turanogryllini crickets (Orthoptera, Gryllidae, Gryllinae) from Cameroon, with identification keys for African species - (:unkn) unknown (My University, 2022)
During a Gryllidae survey in the Southern Cameroonian Plateau, two new species of the tribe Turanogryllini Otte, 1987 were discovered and described, namely Turanogryllus zamakoensis Um Nyobe, Kekeunou & Bilong Bilong sp. nov. and Neogryllopsis gorochovi Um Nyobe, Kekeunou & Ma sp. nov. This finding extends the known distribution of the genera Turanogryllus Tarbinsky, 1940 and Neogryllopsis Otte, 1983. New environments are also recorded for these crickets, and an identification key for African species is proposed for these two genera. Résumé Au cours d'une étude des Gryllidae dans le Plateau Sud Camerounais, deux nouvelles espèces de la tribu Turanogryllini Otte, 1987 ont été découvertes et décrites, à savoir Turanogryllus zamakoensis Um Nyobe, Kekeunou & Bilong Bilong sp. nov. et Neogryllopsis gorochovi Um Nyobe, Kekeunou & Ma sp. nov. Cette découverte élargie l'aire de répartition connue des genres Turanogryllus Tarbinsky, 1940 et Neogryllopsis Otte, 1983. De nouveaux environnements ont été également signalés pour ces grillons et une clé de détermination est proposée pour les espèces africaines de ces deux genres.
Keywords: African Research